Recent warming and decadal variability of Gulf of Maine and Slope Water. Issue 9 (27th July 2021) - Seidov, Dan; Mishonov, Alexey; Parsons, Rost
Abstract: The oceanographic conditions in the Gulf of Maine, Scotian Shelf, Slope Sea, and surroundings are determined by interplay of two major circulation systems—the Gulf Stream and Labrador Current. This study aims to better understand regional long‐term climate trends caused by the Gulf Stream decadal variability. The in situ data analysis confirms a continuous slow warming within all three areas over the last five decades. It is shown that the warming accelerated in the recent 10 years coinciding with a strengthened northward incursion of warm water in the summer months. Such strong northward migration of warm water was not seen in the four preceding decades, making the current rapid warming different from previous ones. We argue that the recent decadal‐scale warming is unique and may signal that the shift of the thermal regime in this region may be at least partially caused by a changed pattern of the Gulf Stream extension zone's long‐term variability. We found that the Scotian Shelf and Slope Water region has recently been warming much faster than the Gulf of Maine, both in the subsurface (the upper 50 m) and in deeper layers, indicating that the probable cause of the faster warming in the most recent decade is due to the regime change in the Gulf Stream extension region.